PROBLEM FILOZOFICZNEGO UJĘCIA ISTOTY BOGA W SUMMA THEOLOGIAE ŚW. TOMASZA Z AKWINU. PERSPEKTYWA EGZYSTENCJALNA - Andrzejuk, Artur (Studia Theologica Varsaviensia, 2018)
The „second way” in the famous third article of Summa theologiae most closely corresponds to all of Thomas’s own investigation into the existence of God. On several occasions, when referring to its conclusion („there is a first effective cause”), Aquinas adds that the first cause is its own esse. The attributes of God are the consequences of His structure as the esse itself. The first is that God is a one-element being, in which existence is the only ontic material, and it has the nature of an act. It follows that existence is identified with an essence of God, His nature, life and all that God can be predicted („divinity” – deitas). God is understood to be the cause of all other beings, and He is not caused. This is what we call „subsistence” (ipsum subsistens). God’s immutability and eternity are simple consequences of His subsistent existence. God’s infinity and omnipresence are the derivative attributes of His existence. The whole group of such attributes can be recognized as the consequences of his structure of the subsistent act of existence. The second group of attributes of God is the attributes which manifest the existence of being. As such, they concern every being. However, the existence of God has absolute character as well as its attributes which manifest the existence. In relation to God, Thomas mentions here such attributes as the good, the truth, the unity, but there is no doubt that we can attribute to God the rest of transcendentals: reality, distinctiveness and beauty. Aquinas – basing here on metaphysical principle of proportionality of cause and effect – sees the source of perfection in God. From this perspective we can talk about the personal nature of God, that is, His reasoning, freedom and love. Also, Thomas does not reject the existential perspective. Within its framework, he solved the paradox of the omnipotence of God (can God create something more perfect than Himself?). Aquinas associates the concept of God’s omnipotence with existence and states that it consists in the possibility of creating every being that can exist. This means that God does not contribute contradictory ontological internal structures. Thus, we can say that Thomas Aquinas in Summa theologiae outlines a coherent and quite complete conception of the essence of God, which is built within his existential theory of existence.